A Social Network Lens to Community Health Worker Influence and Impact - Reza Yousefi Nooraie; Deniz Naghibi; Ruthmarie Hernández-Torres; Paula Cupertino (Journal of Primary Care & Community Health)
Community Health Workers (CHWs) are members of healthcare teams that are integrated in, and often share language, beliefs, and lived experiences with their communities. They use their formal and informal social networks to promote healthy behavior, to connect community members to resources, and to build more resilient community networks. We propose a framework to conceptualize CHW interventions aiming to operationalize and optimize CHW social relations and networks. CHW-mediated network interventions can focus on the dissemination and diffusion of health messages, using the channels of trust and formal and informal relations, as well as, engaging communities to enhance the cascade of spreading/diffusion. Network interventions can also focus on network-building and community dialog, relying on the role of CHWs in bringing the community members together in facilitating conversation, promoting social justice and inclusion, and mobilizing the community in collective action. In addition, the network interventions can aim for boundary-spanning and bridging activities, to facilitate the community’s access to health services and external resources, as well as bringing the community voice to health systems to influence priorities and policies. Similar to any other complex interventions, CHW network interventions should be fine-tuned and adapted to local and community needs, capacities, and network structures, and actively involve community members in the conceptualization, delivery, and evaluation.